2011
DOI: 10.1103/physrevd.83.124020
|View full text |Cite
|
Sign up to set email alerts
|

Generalized spinfoams

Abstract: We reconsider the spinfoam dynamics that has been recently introduced, in the generalized Kamiński-Kisielowski-Lewandowski (KKL) version where the foam is not dual to a triangulation. We study the Euclidean as well as the Lorentzian case. We show that this theory can still be obtained as a constrained BF theory satisfying the simplicity constraint, now discretized on a general oriented 2-cell complex. This constraint implies that boundary states admit a (quantum) geometrical interpretation in terms of polyhedr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
196
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(204 citation statements)
references
References 70 publications
8
196
0
Order By: Relevance
“…In that case it has been shown [40] that (4.30) is still satisfied. This second possibility is still compatible with the classical limit but is weaker than the previous one.…”
Section: Jhep05(2011)016mentioning
confidence: 78%
“…In that case it has been shown [40] that (4.30) is still satisfied. This second possibility is still compatible with the classical limit but is weaker than the previous one.…”
Section: Jhep05(2011)016mentioning
confidence: 78%
“…At the same time, the U A (1)-symmetry still appears to be broken. The large lattices used in our study also offer the possibility to study plasma properties in terms of temporal correlation functions in the vector channel and the associated spectral function (see [29]). A first study has already been reported at conferences and we refer to our future publication for the details.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting space-time structure has been investigated in [13]. The additional restriction to r = 0 does not provide any modification on the statements above about the consistency of the procedure to solve constraints.…”
Section: Second-class Constraints On a Quantum Levelmentioning
confidence: 99%
“…While in the whole phase-space the induced symplectic structure is trivial, once the restriction to the hypersurfaces (13) takes place the following Poisson brackets are induced…”
Section: Bf Theories Vs Lqg Without the Time Gaugementioning
confidence: 99%